Influence of customized cooking methods on the phenolic contents and antioxidant activities of selected species of oyster mushrooms (Pleurotus spp.) - Tan, Yee Shin; Baskaran, Asweni; Nallathamby, Neeranjini; Chua, Kek Heng; Kuppusamy, Umah Rani; Sabaratnam, Vikineswary (Springer Verlag (Germany), 2015)
Nutritional value of cooked food has been considered to be lower compared to the fresh produce. However, many reports showed that processed fruits and vegetables including mushrooms may retain antioxidant activity. Pleurotus spp. as one of the edible mushroom are in great demand globally and become one of the most popular mushrooms grown worldwide with 25-fold increase in production from 1960–2009. The effects of three different cooking methods (boiling, microwave and pressure cooking) on the antioxidant activities of six different types of oyster mushrooms (Pleurotus eryngii, P citrinopileatus, P. cystidiosus P. flabellatus, P. floridanus and P. pulmonarius) were assessed. Free radical scavenging (DPPH) and reducing power (TEAC) were used to evaluate the antioxidant activities and the total phenolic contents were determined by Folin-Ciocalteu reagent. Pressure cooking improved the scavenging abilities of P. floridanus (>200 %), P. flabellatus (117.6 %), and P. pulmonarius (49.1 %) compared to the uncooked samples. On the other hand, the microwaved Pleurotus eryngii showed 17 % higher in the TEAC value when compared to the uncooked sample. There was, however, no correlation between total phenolic content and antioxidant activities. There could be presence of other bioactive components in the processed mushrooms that may have contributed to the antioxidant activity. These results suggested that customized cooking method can be used to enhance the nutritional value of mushrooms and promote good health.